Growth Performance and Carcass Characteristics of Lambs Fed Concentrate Mixtures Containing Varying Levels of Palm Oil Decanter Cake - Devika, Dharmana; Kishore, Konka Raja; Kumar, Dhulipalla Srinivas; Seshaiah, Chappidi Venkata (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
A study was conducted to evaluate the effect of feeding concentrate mixture containing varying levels of palm oil decanter cake (PODC)on growth performance and carcass characteristics in Nellore brown ram lambs. In a completely randomized design, 18 lambs weredivided into three equal groups of six each and allotted to three dietary treatments (T1 T2 and T3) comprising of green fodder SuperNapier and concentrate mixture (20% CP) containing PODC at 0, 10, and 20%, respectively. The body weight gain (kg) and average dailygain (g/d) of lambs improved significantly (p
Keywords: Carcass characteristics; Growth performance; Palm oil decanter cake; Nellore brown rams lambs